Assessment of bone marrow-derived mesenchymal stem cells capacity for odontogenic differentiation and dentin regeneration in methimazole-treated albino rats (Light microscopic Study) - Amany A. Rabea (Saudi Dental Journal)
Background: Methimazole is an antithyroid drug. It has side effects on many tissues. Bone marrow-derived mesenchymal stem cells (BM-MSCs) are promising in the field of tissue regeneration. Objective: To investigate the capacity of BM-MSCs on odontogenic differentiation and dentin regeneration at different time intervals in methimazole treated rats. Methods: Twenty-eight male albino rats were classified as: Group I: got distilled water. Group II: obtained therapeutic dosage of methimazole as pro-drug “Neo-Mercazole®”. Group III: received methimazole then solitary injection of BM-MSCs at day 21. Group IV: obtained methimazole and single injection of BM-MSCs at the beginning of the experiment. Light microscope was used to examine specimens. Recently formed collagen and β-catenin-immunoreactivity area% were appraised histomorphometrically and statistically. Results: Histological examination of odontoblasts and dentin illustrated normal structure in Group I and nearly normal features in Group IV. Group II demonstrated discontinuation of odontoblastic layer and areas of different stainability in dentin. Group III showed an evidently wide layer of odontoblast-like cells and distinct dentinal tubules. Masson's trichrome results of dentin in Groups I &IV showed apparently equal areas of new and old collagen. Group II illustrated old collagen mainly. Group III explored new collagen only. β-catenin-immunoreactivity was strong in Groups I & IV, mild in Group II and moderate in Group III. Statistical results revealed that the highest mean of newly formed collagen area% was in Group III, followed by Group I, Group IV then Group II respectively. Regarding β-catenin-immunoreactivity area%, the highest mean was recorded in Group I, subsequently Group IV, next Group III then Group II. Conclusions: Methimazole has destructive consequences. BM-MSCs have a time-based increased capacity for odontogenic differentiation and regeneration of dentin.